Social Innovation for Food Security and Tourism Poverty Alleviation: Some Examples From China - Huang, Guo-Qing; Tsai, Fu-Sheng (Frontiers in Psychology, 2021)
The COVID-19 pandemic has brought hunger to millions of people around the world. Social distancing measures coupled with national lockdowns have reduced work opportunities and the overall household incomes. Moreover, the disruption in agricultural production and supply routes is expected to continue into 2021, which may leave millions without access to food. Coincidentally, those who suffer the most are poor people. As such, food security and tourism poverty alleviation are interlinked when discussing social problems and development. While the corporate interest in tourism poverty alleviation is as old as the industrial revolution, little research has been conducted to show how social innovation can be leveraged to reinforce food security and alleviate poverty. Thus, this case study examines the food industry in rural China to establish how it conducts social innovation in food production and distribution to facilitate social development and mitigate poverty.